Penerapan Platform Thunkable untuk Pengembangan Aplikasi Edukasi Tokoh Politik dalam Pembelajaran PKN di SMA Ampera Kota Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Irwan Soulisa; Rindaldy Rindaldy; Fransina Fransina; Christine Christine; Akbar Akbar (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
The advancement of digital technology has driven significant transformation in the field of education, particularly in the innovation of learning media that is interactive and easily accessible to students. The subject of Pancasila and Civic Education (PPKn), as a crucial component of character education, must adapt to these developments to ensure that the material remains relevant and engaging for today’s digital generation. This community service activity aimed to enhance students' learning motivation by conducting a training program on creating educational applications using the no-code platform Thunkable. The focus of the training was on the topic of national political figures, which is part of the core competencies in the PPKn curriculum. The activity was held at SMA Ampera in Sorong City, involving 11th-grade students as active participants. A participatory and project-based learning (PjBL) approach was employed, in which students were guided to design, create, and test their own educational applications based on their ideas and creativity. The program was carried out in three stages: preparation (developing modules, training materials, and technical setup), training and practice (introduction to the Thunkable platform, interface design, and basic programming), and testing and evaluation (application trials by other students and effectiveness assessment). The results of the activity showed a significant increase in students' learning motivation, basic digital skills, and active engagement in the learning process. The participants successfully created educational application prototypes featuring visual content, brief narratives, and interactive quizzes about national political figures. Moreover, students demonstrated collaborative attitudes, innovation, and confidence when presenting their work. This activity demonstrates that a project-based learning approach supported by Thunkable technology can be an effective alternative for creating meaningful, contextual, and empowering learning experiences. It is especially beneficial for schools with limited access to digital technology. By integrating creativity and digital tools into civic education, students are encouraged to become not only technologically literate but also more engaged in understanding national identity and political history in a modern, accessible way.